A moralidade do senso comum relativa à intervenção compulsória para biomelhoramento moral modificada pelo conhecimento: caminhos de Bertrand Russell - Rosario, Marcelle Coelho do (Universidade do Vale do Rio dos Sinos, 2019)
The morality of the common sense will change, the mankind will progress morally, regarding the acceptance of the compulsory moral improvement in the face of the information contained in the scientific knowledge and after the reflection on the results of such intervention fully in agreement with now considered moral by the societies which they integrate, democratically governed. Therefore, this work will, using literature review, find ways to distinguish human enhancement from human “improvement”; adjust the concept of human improvement within antagonist theories, in order to facilitate studies and understanding of the proposed distinction between enhancement and treatment; describe the moral concerns of each theory through its hard aspects, and raise Davis Ross's theory of prima facie duties as a first possibility of justifying the enhancement intervention. As well as, to examine the concept of moral bio-enhancement from the transhumanist and bio-conservative aspects; determine and delimit the scope of its application, and a possible related justification; to ask whether or not moral enhancement should be compulsorily administered to society, as Ingmar Persson and Julian Savulescu have argued; to observe the proposals for the creation of a “global government” aiming at the avoidance of the “Last Damage” in support of the compulsory moral enhancement of the population; to express the only possibilities in which it is understood that the compulsory nature of bio-enhancing moral intervention could be commendable, pointing to three specific cases, namely: replacing the restrictive penalty of liberty; for predictions of high criminal levels, and as a basic requirement for individuals wishing to run for political office. Still, there are questions to be asked about the possible risks and benefits, and whether the moral improvement would be desirable and effective, given the existence of the optimal moral Pareto. Finally, the argumentative framework used by Bertrand Russell in Religion and Science (2009) will be applied to the clash of common sense morality and compulsory moral improvement, aiming to obtain a result similar to that revealed by Russell, meaning that knowledge is capable of modifying the morality of common sense.
Keywords: Biomelhoramento humano; Biomelhoramento moral; Bioconservadorismo; Transumanismo; Caráter compulsório; Human bio-enhancement; Moral improvement; Bioconservatism; Transhumanism; Compulsory character; ACCNPQ::Ciências Humanas::Filosofia